The Impact of Defoliation on the Age of King Grass (Pennisetum purpuphoides) on Ultisol Soil - Aini, Qurrata; Sriagtula, Riesi; Jamarun, Novirman; Yanti, Gusri; Suyitman, Suyitman (Universitas Bengkulu, 2026)
King grass production can be increased by extending the defoliation period because king grass will not flower unless it is planted in cold (subtropical) areas, so its vegetative phase is longer. This study aims to determine the optimal defoliation age in terms of growth, production, and chemical composition of king grass (Pennisetum purpuphoides) at the first harvest on ultisol soil. Treatments include A: defoliation at 60 days after planting (DAP); B: 90 DAP; C: 120 DAP. Parameters observed included plant growth, production, nutrient and fibre fractions, and total digestible nutrient (TDN). This research was conducted experimentally using a group-randomized design (GRD) with three treatments and four replications. The results showed that treatments for plant height, number of tillers, fresh production, dry matter (DM), and fibre fraction content had a highly significant effect (P < 0.01). In contrast, the treatments showed a non-significant effect (P>0.05) on silica and TDN. Based on the results, it can be concluded that the optimum growth, production, and quality of king grass cultivated on ultisol soil is at the age of 90 DAP defoliation, with fresh production of 60.28 ton/ha/harvest, crude protein is 11.68%, lignin is 8.88%, and TDN is 61,23%.